Between Livy and Tacitus: An Approach to Classical Latin Historiographical Models in the Work of Inca Garcilaso (Revista de Crítica Literaria Latinoamericana, 2017)
The literary works of Inca Garcilaso de la Vega are a conscious historiographical program with a clear model, in our opinión: the Roman historian Tacitus. In this paper, I approach this hypothesis with three evidences: the classical studies of the Inca, the rhetoric, and the parallelism between Tacitus’s and Garcilaso’s historical works.
Keywords: Inca Garcilaso; Tacitus; historiography; rhetorics